Quantitative literature analysis on efficacy and safety of balloon-occluded transarterial chemoembolization for hepatocellular carcinoma - Wei Fan Sui; Yu Xin Duan; Ze Feng Cai; Jian Yun Li; Jian Hua Fu (BMC Gastroenterology)
Abstract Aim To analyze the efficacy and safety of balloon-occluded transarterial chemoembolization (B-TACE) of hepatocellular carcinoma (HCC). Methods We searched English databases, assessed the quality of the selected studies, analyzed the extracted data, tested heterogeneity of data, explored the resources of heterogeneity, and tested publication bias. Results After inclusion and exclusion criterion, totally 7 studies included in our analysis. The numbers of complete response (CR) in B-TACE were significantly more than in Non B-TACE (P = 0.003). There were no significant difference in partial response (PR), stable disease (SD) and progressive disease (PD) between B-TACE and Non B-TACE. Moderate heterogeneity existed in CR and PR (I2 = 60%). Low heterogeneity existed in SD (I2 = 36%). Heterogeneity did not exist in PD (I2 = 0%). The numbers of treatment effect (TE) 4–1 in B-TACE were significantly more than in Non B-TACE, respectively (P = 0.000007, P < 0.00001). Heterogeneity did not exist in TE4 (I2 = 0%). Low heterogeneity existed in T3 - 1 (I2 = 48%). The numbers of post embolization syndrome(PES) in B-TACE were significantly more than in Non B-TACE, respectively(P = 0.000007, P < 0.00001). There were no significant difference in adverse events (AEs) of grade 3 and 2 between B-TACE and Non B-TACE, respectively(P = 0.57, 0.12). High heterogeneity existed in PES (I2 = 76%). Moderate heterogeneity existed in AEs of grade 2(I2 = 57%). Heterogeneity did not exist in AEs of grade 3(I2 = 0%). Conclusion B-TACE was safe. It showed promising efficacy in achieving higher CR rates in short term compared to Non B-TACE.